AN ANALYSIS OF CODE MIXING USED BY JUDGES IN MASTER CHEF INDONESIA SEASON 5 - Fadli Luthfi; Jismulatif Jismulatif; Erni Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study seeks to search the types of code mixing and the dominant of code mixing which are often used the television program in Master Chef Indonesia Season 5. In this study research, descriptive analysis and documentation method were applied. The finding discovers that the types of code mixing which had been observed in the television program are the intra- sentential code mixing 89%, intra-lexical code mixing 11%, and involving a change pronunciation 0% in Master Chef Indonesia Season 5.Keywords: Analysis, Code-Mixing, Television program, Master Chef Indonesia Season 5